Prevalence and patterns of coronary artery disease in patients undergoing cardiac surgery for rheumatic and non- rheumatic valvular heart disease in a tertiary care center of Nepal - Sahi, Ravi; Sayami, Arun; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Thapa, Sanjeev; Khanal, Rajaram; Devkota, Surya; Shakya, Abhishesh; Shakya, Sheelendra (Nepalese Heart Journal, 2018)
Background and Aims: Coronary artery disease (CAD) constitute a major cause of cardiovascular morbidity and mortality worldwide with an enormous burden on healthcare resources. Prevalence and pattern of CAD in patients of rheumatic and non-rhemuatic valvular heart diseases varies widely with limited data on optimal strategies for diagnosis and treatment.Methods: This study includes 97 patients with rheumatic and non-rheumatic valvular heart disease who underwent coronary angiogram (CAG) before cardiac surgery. Patients were divided into two groups based on rheumatic heart disease (RHD) & non-rheumatic disease (Non-RHD) and correlate the patterns of CAD.Results: Out of 97 patients, 22 (22.6%) patients were found to have significant CAD. In patients with non-rheumatic origin CAD was common (15 patients, 68.1%) as compared to rheumatic origin (7 patients, 31. 8%). In rheumatic origin, the prevalence was 7(12.2%) out of 57 patients while in non-rheumatic origin, was 15(37.5%) out of 40 patients. In RHD group, all patients with CAD were found to have single vessel diease (SVD) while, in non-RHD group, 11 patients (73.3%) had SVD, 3 patients (16.7%) had double vessel disease (DVD) and one patient (5.6%) had triple vessel disease (TVD).Conclusions: Prevalence of CAD is higher in patients with non-RHD in comparison to those with RHD. We also found SVD to be the most common pattern of CAD in both rheumatic and non-rheumatic valvular heart disease.